All-solid-state electrolyte membrane and preparation method and application thereof

By using polysilazane with a specific structure as a binder and combining a binder to a promoter, the problem of insufficient adhesion and solubility of the all-solid electrolyte film is solved, and the safety performance and ionic conductivity of the battery are improved.

CN119852501AActive Publication Date: 2025-04-18GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411714747.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing adhesive for all-solid electrolyte membrane reacts with the sulfide electrolyte, has poor solubility and poor adhesion, resulting in poor mechanical performance and difficult to meet actual needs.

Method used

Polysilazane (PSZ) with a specific structure is used as the binder, and combined with the binder to improve adhesion and solubility, and does not react sideways with the sulfide electrolyte.

Benefits of technology

The bonding strength, heat resistance, hydrophobicity and mechanical properties of the all-solid electrolyte membrane are improved, and the safety performance and ionic conductivity of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention provides an all-solid-state electrolyte membrane as well as a preparation method and application thereof, the all-solid-state electrolyte membrane comprises the following raw materials in parts by weight: 1-10 parts of a binder, and the binder is polysilazane with a specific structural formula. According to the all-solid-state electrolyte membrane provided by the invention, polysilazane with a specific structure is adopted as the binder, so that the bonding strength of the binder is effectively improved, and the safety performance of a battery is improved; the obtained all-solid-state electrolyte membrane is high in ionic conductivity, and the moisture resistance of the all-solid-state electrolyte membrane is remarkably improved. The all-solid-state electrolyte membrane provided by the invention can also comprise 90-99 parts of a solid-state electrolyte; the all-solid-state electrolyte membrane can further comprise 0-5 parts of an auxiliary binding agent, and the mechanical property of the all-solid-state electrolyte membrane is improved by virtue of the flexibility brought by high molecular weight of the auxiliary binding agent. According to the all-solid-state electrolyte membrane, the performance of an electrode, a solid-state battery and an electric device which are obtained by adopting the all-solid-state electrolyte membrane is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid electrolytes, and in particular to an all-solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] With the popularity of new energy vehicles, lithium-ion batteries have also been promoted. However, lithium-ion batteries currently have serious safety hazards, which limits their application in electric vehicles. The lithium-ion batteries commonly used now are liquid batteries based on flammable carbonate solvents, which will quickly ignite and cause fires after thermal runaway occurs.

[0003] Semi-solid batteries made by using all-solid-state electrolytes instead of flammable organic solvents can effectively increase the thermal runaway temperature and reduce the heat release after thermal runaway. They are considered to be the ultimate solution to the safety problems of lithium-ion batteries.

[0004] The literature (A Three-Dimensional Fiber-Network-Reinforced Composite Solid-State Electrolyte from Waste Acrylic Fibers for Flexible All-Solid-State Lithium Metal Batteries) re-dissolves acrylic yarns from discarded clothing, and loads LLZTO ceramic nanoparticles into acrylic-based nanofibers through electrospinning technology to construct an acrylic-based ceramic composite nanofiber solid electrolyte (LLZTO / acrylic electrolyte) with 3D fiber network reinforcement. This solid electrolyte has good electrochemical stability (5.44V vs. Li+ / Li, Li / Li battery is stable for 2350h without short circuit). However, its ionic conductivity is low (3.61 × 10 at 50°C). −4 S / cm), which is difficult to meet the actual needs. This is because the solid electrolyte used is an oxide solid electrolyte with poor ion conductivity. Compared with oxide electrolytes, sulfide electrolytes have ultra-high lithium ion conductivity (>10 -3S / cm), the literature (Stable Binder Boosting Sulfide Solid Electrolyte Thin Membrane for All-Solid- State Lithium Batteries) analyzed the reaction of sulfide electrolyte Li6PS5Cl with different solvents and found that Li6PS5Cl would produce serious side reactions with most high-polarity solvents (acetone, dimethylacetamide, etc.). Although low-polarity solvents do not react with sulfide electrolytes, it is difficult for them to dissolve binders with high molecular weight or high polarity groups. In addition, when selecting binders for sulfide electrolytes, groups that react with sulfide electrolytes (such as carboxyl, hydroxyl, etc.) are usually avoided, which usually results in the binding force of the binder not meeting actual needs. In addition, sulfide electrolyte membranes also have the defect of being unstable to water and demanding production conditions. Therefore, developing a binder for all-solid electrolyte membranes that has good adhesion, good solubility, and does not react with sulfide electrolytes is a technical problem that the industry is currently working to solve.

[0005] The Chinese patent application CN115602914A discloses a sulfide solid electrolyte membrane, which uses Li6PS5Cl as electrolyte, n-heptane as dispersant, and hydrogenated styrene-butadiene block copolymer (SEBS) as binder. However, SEBS lacks polar groups on its molecular chain, and its bonding force is only provided by the entanglement of polymer molecular chains, so its bonding force is poor, and the mechanical properties of the prepared electrolyte membrane are poor. Summary of the invention

[0006] In order to solve the problems of the above prior art that the binder for the all-solid electrolyte membrane reacts with the sulfide electrolyte, has poor solubility, and has poor bonding strength, the present invention provides an all-solid electrolyte membrane, wherein the raw materials thereof include 1-10 parts of a binder by weight, and the binder is a polysilazane having the following structural formula: Wherein, R1 and R2 are respectively one of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, vinyl, allyl, methylamino, hydrogen atom, trifluoromethyl, and pentafluoroethyl; n≥10.

[0007] Polysilazane (PSZ) is a type of polymer whose main chain consists of nitrogen-silicon bonds. It has good heat resistance, adhesion, and hydrophobicity and is used in ceramic material precursors, hydrophobic coatings, aerospace materials and other fields. In the field of batteries, it is often used as a polysilazane electrolyte. In the present invention, polysilazane is used as a binder, which not only has good adhesion, but also has good solubility and does not react with electrolytes (such as sulfide electrolytes). While improving adhesion, it will not affect the ionic conductivity of the all-solid-state electrolyte membrane; at the same time, the use of polysilazane with the structure unexpectedly produces a gain effect such as improving the thermal stability and hydrophobicity of the electrolyte.

[0008] In some embodiments of the present invention, R1 is selected from one of methyl and propyl; R2 is selected from one of ethyl, butyl and vinyl.

[0009] In some embodiments of the present invention, R1 is a methyl group, and R2 is selected from an ethyl group and a vinyl group.

[0010] In some embodiments of the present invention, R1 is propyl and R2 is butyl.

[0011] In some embodiments of the present invention, the raw material further includes 90-99 parts by weight of a solid electrolyte; preferably, the solid electrolyte is selected from at least one of oxides, sulfides, and polymers; in particular, the all-solid-state electrolyte membrane is preferably a sulfide with the highest ionic conductivity.

[0012] In some embodiments of the present invention, the raw materials further include 0-5 parts by weight of an auxiliary binder. Preferably, the auxiliary binder is selected from at least one of styrene-ethylene butylene-styrene copolymer, styrene butadiene rubber, polytetrafluoroethylene, polyisobutylene, nitrile rubber, polyvinyl butyral, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate, polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid and polyacrylonitrile.

[0013] The all-solid electrolyte membrane provided by the present invention uses polysilazane as a binder to enhance the bonding force, improve the solubility and prevent the electrolyte from reacting, and also improves the mechanical properties of the all-solid electrolyte membrane by adding an auxiliary binder and utilizing the flexibility brought by the high molecular weight of the auxiliary binder.

[0014] In some embodiments of the present invention, the all-solid electrolyte membrane comprises 90-99 parts of solid electrolyte, 1-10 parts of binder and 0-5 parts of auxiliary binder by weight; preferably the total amount is 100 parts.

[0015] In the present invention, the solid electrolyte, polysilazane binder and auxiliary binder in the above specific proportions are used to simultaneously improve the bonding force and solubility without reacting with the electrolyte, and the auxiliary binder improves the mechanical properties of the all-solid electrolyte membrane by virtue of the flexibility brought by the high molecular weight.

[0016] The second object of the present invention is to provide a method for preparing the aforementioned all-solid electrolyte membrane, comprising: (1) preparing electrolyte slurry; (2) Using a scraper to scrape the slurry to form an electrolyte membrane; (3) Transferring the electrolyte membrane to an inert gas-protected oven for drying; (4) After drying, the film is peeled off and the electrolyte membrane is rolled; (5) Cutting the electrolyte membrane to obtain an all-solid-state electrolyte membrane of a target size.

[0017] In some embodiments of the present invention, in step (1), the solvent of the electrolyte slurry is selected from at least one of n-heptane, n-pentane, hexane, cyclohexane, n-butyl ether, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, methyltetrahydrofuran, and ethyl acetate.

[0018] In some embodiments of the present invention, the drying temperature in step (3) is 30-100° C., and / or the drying time is 2-24 h.

[0019] A third aspect of the present invention provides an electrode for a solid-state battery, which uses the aforementioned all-solid-state electrolyte membrane.

[0020] A fourth aspect of the present invention provides a solid-state battery using the electrode. The solid-state battery may be a battery cell, a battery module or a battery pack.

[0021] A fifth aspect of the present invention provides an electrical device, the solid-state battery. The solid-state battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0022] In some embodiments, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0023] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.

[0024] The beneficial effects of the present invention are as follows: 1. There are hydrogen bond interactions between polysilazane molecules, which can effectively improve the bonding strength of the adhesive.

[0025] 2. Polysilazane has good heat resistance and can maintain structural integrity and mechanical properties at high temperatures, thereby improving the safety performance of the battery.

[0026] 3. Polysilazane has good solubility and can be well dissolved in low-polarity solvents including alkanes.

[0027] 4. There is no side reaction between polysilazane and sulfide electrolyte, and the lithium ion conductivity of the all-solid electrolyte membrane will not be significantly reduced.

[0028] 5. Polysilazane has extremely strong hydrophobicity and can significantly improve the moisture resistance of the all-solid-state electrolyte membrane.

[0029] 6. Polysilazane is combined with a co-binder. On the basis of using polysilazane as a binder to improve adhesion, solubility and not react with the electrolyte, the mechanical properties of the all-solid electrolyte membrane are further improved by virtue of the flexibility brought by the high molecular weight of the co-binder. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] In the following embodiments, the weight unit is g, and in fact 1 g = 1 part, such as 4 g of PSZ and 1 g of NBR, that is, 4 parts of PSZ and 1 part of NBR, and so on. It can also be expressed as the mass ratio of PSZ to NBR is 4:1, and so on.

[0033] In the following examples, the polysilazane used has the following structure: , Here, n is 800.

[0034] Example 1 This embodiment provides an all-solid electrolyte membrane, the raw materials of which include: 4 g of PSZ (R1 and R2 are methyl and ethyl, respectively), 1 g of NBR, and 95 g of Li6PS5Cl.

[0035] This embodiment also provides a method for preparing the all-solid electrolyte membrane, comprising: Step (1): In a glove box, PSZ (R1 and R2 are methyl and ethyl, respectively), NBR, Li6PS5Cl, and n-butyl ether in a mass ratio of 4:1:95 are mixed and added into a homogenizer to prepare a slurry; Step (2): using a scraper of a certain thickness to scrape the slurry; Step (3): transfer the electrolyte membrane to an oven protected by an inert (helium) gas and dry it at 60°C for 7 h; Step (4): after drying, peel off the electrolyte membrane and roll the electrolyte membrane to a certain thickness; Step (5): cutting the electrolyte membrane to obtain an all-solid electrolyte membrane of a target size.

[0036] Example 2 This embodiment provides an all-solid electrolyte membrane, which is basically the same as Embodiment 1, except that R1 and R2 in PSZ are propyl and butyl, respectively.

[0037] Example 3 This embodiment provides an all-solid electrolyte membrane, which is basically the same as Embodiment 1, except that its raw materials include: 3 g of PSZ (R1 and R2 are methyl and ethyl, respectively), 2 g of SEBS, and 95 g of Li6PS5Cl.

[0038] Example 4 This embodiment provides an all-solid electrolyte membrane, which is basically the same as Embodiment 1, except that its raw materials include: 3 g of PSZ (R1 and R2 are methyl and vinyl, respectively), 2 g of SEBS and 95 g of Li6PS5Cl.

[0039] Example 5 This embodiment provides an all-solid electrolyte membrane, which is basically the same as the embodiment 1, except that its raw materials include: PSZ and Li6PS5Cl in a mass ratio of 5:95, no auxiliary binder is added, and the solvent used is n-heptane.

[0040] Comparative Example 1 This comparative example provides an all-solid electrolyte membrane, which is basically the same as Example 1, except that 3 g of PSZ (R1 and R2 are methyl and ethyl, respectively) is replaced by NBR in equal amounts, that is, its raw material composition is: 5 g of NBR and 95 g of Li6PS5Cl.

[0041] Test example Test object: All-solid electrolyte membranes obtained in various embodiments and comparative examples Experimental method: The all-solid-state electrolyte membrane obtained in each embodiment and comparative example is used to assemble a stainless steel / all-solid-state electrolyte membrane / stainless steel mold battery and perform an AC impedance test to calculate the ionic conductivity; a contact angle analyzer is used to measure the water contact angle of the all-solid-state electrolyte membrane to characterize its hydrophobicity. The larger the contact angle, the better the hydrophobicity; a universal testing machine is used to measure the tensile strength of the all-solid-state electrolyte membrane to characterize the bonding force. The larger the tensile strength, the better the bonding force; the all-solid-state electrolyte membrane obtained in each embodiment and comparative example is used to assemble an NCM / all-solid-state electrolyte membrane / SiOx soft-pack battery and a hot box experiment is performed to characterize its thermal stability.

[0042] Test results: The water contact angle of the all-solid electrolyte membrane, the ionic conductivity of the assembled battery and the hot box runaway temperature are shown in Table 1.

[0043] Table 1

[0044] Note: " / " in the table means no addition It can be seen from Table 1 that (1) compared with the comparative example, the all-solid electrolyte membrane using the embodiment of the present invention has better hydrophobicity and adhesion, especially the all-solid electrolyte membranes obtained in Examples 1 and 5 have significantly better adhesion, and the all-solid electrolyte membranes obtained in Examples 1-5 all have significantly better hydrophobicity; (2) the battery obtained by using the all-solid electrolyte membrane provided by the embodiment of the present invention has better ionic conductivity and thermal stability, indicating that the use of the all-solid electrolyte membrane provided by the present invention can significantly improve the ionic conductivity and service life of the battery; (3) by comparing Example 1 with Comparative Example 1, it can be seen that under the same other conditions, only the difference in PSZ can significantly improve the hydrophobicity of the all-solid electrolyte membrane and the ionic conductivity and thermal stability of the battery; (4) the solvent used in Example 5 is n-heptane, while the co-binders such as NBR and SEBS cannot be dissolved in n-heptane, indicating the superior solubility of PSZ; (5) the lithium ion conductivity of the sulfide electrolyte does not decrease significantly (compared with the ionic conductivity of the sulfide electrolyte Li6PS5Cl at room temperature is 1.09 mS cm -1 Compared with the above results), it shows that the sulfide has no side reaction with the binder.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An all-solid electrolyte membrane, characterized in that: The raw materials include 1-10 parts of a binder by weight, and the binder is a polysilazane having the following structural formula: Wherein, R1 and R2 are respectively one of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, vinyl, allyl, methylamino, hydrogen atom, trifluoromethyl, and pentafluoroethyl; n≥10。 2. The all-solid electrolyte membrane according to claim 1, characterized in that: R1 is selected from one of methyl and propyl; R2 is selected from one of ethyl, butyl and vinyl; And / or, R1 is methyl, and R2 is selected from one of ethyl and vinyl; And / or, R1 is propyl and R2 is butyl.

3. The solid electrolyte membrane according to claim 1 or 2, characterized in that: The raw materials further include 90-99 parts by weight of a solid electrolyte; Preferably, the solid electrolyte is selected from at least one of oxides, sulfides and polymers.

4. The all-solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The sulfide is selected from Li6PS5Cl, Li 10 GeP2S 12 、Li7P3S 11 At least one of them.

5. The all-solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The raw material further comprises 0-5 parts of an auxiliary binder by weight; Preferably, the auxiliary binder is selected from at least one of styrene-ethylene butylene-styrene copolymer, styrene butadiene rubber, polytetrafluoroethylene, polyisobutylene, nitrile rubber, polyvinyl butyral, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate, polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid and polyacrylonitrile.

6. The all-solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The all-solid electrolyte membrane comprises 90-99 parts of a solid electrolyte, 1-10 parts of a binder and 0-5 parts of an auxiliary binder, preferably with a total amount of 100 parts.

7. The method for preparing the all-solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: include: (1) preparing electrolyte slurry; (2) Using a scraper to scrape the slurry to form an electrolyte membrane; (3) Transferring the electrolyte membrane to an inert gas-protected oven for drying; (4) After drying, the film is peeled off and the electrolyte membrane is rolled; (5) Cutting the electrolyte membrane to obtain an all-solid-state electrolyte membrane of a target size; Preferably, in step (1), the solvent of the electrolyte slurry is selected from at least one of n-heptane, n-pentane, hexane, cyclohexane, n-butyl ether, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, methyltetrahydrofuran, and ethyl acetate; Preferably, the drying temperature in step (3) is 30-100° C., and / or the drying time is 2-24 h.

8. A solid-state battery electrode, characterized in that: The all-solid electrolyte membrane according to any one of claims 1 to 6 or the all-solid electrolyte membrane obtained by the preparation method according to claim 7 is used.

9. A solid-state battery, characterized in that: The electrode according to claim 8 is used.

10. An electrical device, characterized in that: The solid-state battery according to claim 9 is used.

Citation Information

Patent Citations

  • Separation of electrolytes

    CN101601150A

  • Polymer electrolyte, solid-state electrolyte film and lithium ion battery

    CN108615937A

  • Gel special for lithium battery semi-solid electrolyte and preparation method of gel

    CN110265715A

  • Electrode active substance, method for producing the electrode active substance, and all-solid battery using electrode active substance

    CN111384400A

  • Electrolyte material and preparation method and application thereof

    CN111883826A